The Effect Of Liquidity And Profitability On Tax Aggressivity With Company Value As A Moderation Variable On The Food And Beverage Company On The Indonesian Stock Exchange - Handayani, Irma; Syafrida Hani; Eka Nurmala Sari (International Journal of Economics and Management, 2024)
This study aims to determine, test, and analyze the effect of liquidity and profitability on tax aggressiveness with firm value as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange. This study uses a quantitative method with an associative approach and collects data in a documentary manner by collecting, recording, reviewing and analyzing secondary data in the form of financial statements of manufacturing companies in the food and beverage sub-sector from 2018-2022. This study took 45 samples using purposive sampling method. The data analysis technique used is descriptive statistics used to explain the data description of all variables and also multiple linear regression analysis and Moderated Regression Analysis (MRA) test. The results of this study indicate that liquidity has a negative and significant effect on tax aggressiveness and profitability has a positive and significant effect on tax aggressiveness.